Modal Analysis and Optimization of Fluid-Structure Coupling for Rotor and Inner Cylinder of Vertical Condensate Pump - He, Xiaofeng; Liu, Xiaofeng; Ma, Yunxiang; Lu, Chengbin; Wu, Yang; Nie, Zhongfu (Recent Patents on Mechanical Engineering, 2024)
Background: Low-frequency resonance is one of the common issues encountered during the variable-frequency operation of condensate water pumps. There have been numerous patents and papers proposing solutions to address the low-frequency resonance problem in condensate water pumps. However, the solutions for resonance problems often need to be tailored to specific circumstances. Methods: Based on the acoustic method, the dynamic model of the rotor and inner cylinder of Jiangsu Guohua Chenjiagang Power Plant 2B condensate pump is established to compare the difference between dry modal and fluid-structure coupling modal, the influence of perpendicularity, concentricity and bearing wear on the natural frequency of rotor is studied. Results: The rotor is rigid under normal conditions. When the bearing is worn, the frequency of the rotor will be greatly reduced and may fall into the frequency conversion operation range to excite resonance. The deviation of perpendicularity and concentricity will not directly lead to the decrease of rotor modal but will lead to the increase of bearing stress, aggravate bearing wear, and then affect the rotor modal. As the inner cylinder only relies on the fixed support at the top, the structure stiffness is low, which may lead to low-frequency resonance. By adding two support structures at the guide vane, the first-order modal frequency of the inner cylinder can be increased from 3.29 Hz to 28.88 Hz, effectively avoiding the operating frequency range of the system. Conclusion: This study can guide the optimization of similar pump structures.
Keywords: resonance